Gender differences in the domains of job satisfaction: a questionnaire survey among doctors - Ali Jadoo, Saad Ahmed (Journal of Ideas in Health, 2020)
Background: The impact of gender differences in the labor market cannot be neglected when studying job satisfaction among doctors. This study aimed to assess the gender differences in a ten-items Warr–Cook–Wall (WCW) job satisfaction scale among Iraqi medical doctors. Methods: A cross-sectional study was conducted between January and June 2014 in Iraq. The multistage sampling technique was recruited to collect the data from 20 health institutions. A total of 576 doctors returned the self-administered questionnaire (response rate= 87.3%). Student t-test and the Pearson correlation tests were used to analyzing the data. Results: Female doctors rated the overall job satisfaction index significantly higher than their peer male colleagues (P <0.001). Findings of student t-test showed a significant gender difference; women doctors appeared more satisfied than men in the freedom to choose the method of working, satisfied with their colleagues and fellow workers, amount of responsibility given to them, income, opportunity to use their abilities, hours of work and the amount of variety in the job. In contrast, the Pearson correlation coefficient results indicated a high satisfaction among male doctors than females in terms of recognition for good work (P =0.02) and the physical working condition (P =0.04), respectively. Conclusion: Analysis of data based on indices rather than the only overall job satisfaction appeared as an efficient method to understand gender differences. The possibility of increasing the representation of women in recognition and awards may raise the level of job satisfaction.